Phenotype Ontologies Traversing All the Organisms (POTATO) workshop: 2nd edition. - Matentzoglu, N; Balhoff, J.P.; Bello, S.M.; Bradford, Y.M.; Carmody, L.C.; Cooper, Laurel D.; Laporte, Marie-Angélique (2019)
The central purpose of this workshop was to bring together users and developers of phenotype ontologies and to provide them with a forum to share, learn and debate. The second edition of the workshop further aimed to address two of the fundamental bottlenecks identified in the course of these community efforts: (1) The Phenotype And Trait Ontology (PATO), an essential driver of inference in phenotype ontologies, has limitations that can make it hard to understand and use in defining phenotypes. For example, textual definitions need to be added and improved, and hierarchies refined to be more intuitive. and (2) The phenotype ontology community needs efficient ways to directly contribute to anatomical and cell concepts in the species-independent anatomy ontology Uberon and the Cell Ontology (CL).